Compulsory voting and TV news consumption: evidence from Brazil - Bruce, Raphael Guinâncio (2015)
Do people acquire more information when they are obligated to participate in elections? This dissertation presents empirical evidence on the effects of compulsory voting laws on the consumption of TV news. In Brazil, the law determines that every literate citizen over the age of eighteen and under seventy at the day of the election is subject to a number of penalties if they don\'t attend the ballots. This provides a natural experiment which allows us to identify the causal effect of being under a compulsory voting regime on information acquisition. Using national survey data on the consumption of media we find that, for those who have been exposed to the law for the first time, compulsory voting has a significant and substantial positive impact on the probability of an individual to watch Brazil\'s main newscast, Rede Globo\'s Jornal Nacional. No impact is found, though, for citizens who transition from the voluntary to the compulsory voting regime when they reach the age of seventy.